The Effect Of Service Quality On Customer Satisfaction At Nike Ardilla Restaurant, Wonomulyo Sub-District - Nasriah , Nasriah; Albar , Albar; Asrandi , Asrandi (Fakultas Ekonomi & Bisnis Universitas Muslim Indonesia, 2025)
The increasingly intense competition in the culinary industry demands that every business operator deliver optimal service to maintain customer satisfaction and loyalty. This study examines the extent to which service quality influences customer satisfaction at Nike Ardilla Restaurant, Wonomulyo Sub-district. A quantitative associative approach was employed, using data collected through Likert-scale questionnaires, field observations, and documentation. The sample was determined using the Bernoulli formula, as the total population was unknown (infinite population). Data were analyzed using multiple linear regression. The findings indicate that service quality falls within the “good” category, with an average score ranging from 3.08 to 3.20 on a 4-point scale, while customer satisfaction scores range between 3.16 and 3.18. Regression analysis revealed a positive and significant relationship between service quality and customer satisfaction, with a regression coefficient of 0.255 and a significance value of p = 0.000 (p < 0.05). The R Square value of 0.872 indicates that 87.2% of the variance in customer satisfaction is explained by service quality, while the remaining variance is attributed to other factors. These results confirm that enhancing aspects of service—such as speed, cleanliness, friendliness, and accuracy of service—can significantly improve customer satisfaction. This study provides strategic recommendations for culinary business operators to prioritize service quality as a primary competitive advantage